Of Great Importance - Wijnberg, Nachoem M. (punctum books, 2018)
Of Great Importance is Nachoem Wijnberg's 16th volume of poetry. One of the most prominent living Dutch writers, Wijnberg's poetry is known for its deceptively plain language and his poems, according to the poet himself, can be read well by anyone who can read a newspaper. The poems in Of Great Importance engage with statecraft, economics, and world history, lyricizing taxes and debts, stocks and flows, citizenship and labor contracts, notaries and accountants, factories and strikes, freedoms and fundamental rights, banks and railroads, property rights and codes of honor, sieges and treaties, gods and generals, how to make money and how to win elections, when to declare war and when to found a new state. Wijnberg's engagement with these and other related topics is based on his belief that economics, politics, and history - and all of the tangled relations therein, no matter how asymmetrical - concern how people live together, and his poetry is a creative form of historiography that attends to tracing the theater of an affective commonwealth, in which he builds upon the best work of those thinkers and poets who came before - including Karl Marx, John Maynard Keynes, Heinrich Heine, Czesław Miłosz, and especially C.P. Cavafy. Ultimately, Wijnberg understands that "Something important that changes the world only happens if there is a lever with a fulcrum you cannot know enough about," and yet his poetry gorgeously illuminates this fulcrum.